Traumatic Experiences in Childhood and Maternal Depressive Symptomatology: Their Impact on Parenting in Preschool - María Pía Santelices; María de los Ángeles Fernández; Jaqueline Wendland (MDPI AG, 2022)
The goal of this study is to describe and analyze the relationship between childhood trauma and depressive symptoms and its relation to the parental interactions of mothers (19-47 years) with their 3-4 year old preschool children. Parental interactions, traumatic experiences in mothers' childhood, and current depressive symptoms were measured using the Parenting Interactions with Children: Checklist of Observations Linked to Outcomes (PICCOLO), the Childhood Trauma Questionnaire Short Form (CTQ), and the Beck Depression Inventory (BDI-I), respectively. A nonclinical sample of 81 Chilean mothers with their children was used. Results show that the presence of trauma in mothers' childhood has an impact on parenting; specifically, mothers with an emotional neglect experience showed greater difficulties in adequately promoting autonomy in their children.